2019
DOI: 10.1590/1807-1929/agriambi.v23n4p250-256
|View full text |Cite
|
Sign up to set email alerts
|

Growth and production components of West Indian cherry cultivated with saline waters and potassium fertilization

Abstract: Due to water limitations in terms of both quantity and quality in the semi-arid region of northeastern Brazil, the use of waters with high concentrations of salts become necessary in irrigated agriculture. Thus, this study aimed to evaluate the growth and production of grafted West Indian cherry under saline water irrigation and potassium fertilization. The experiment was carried out in drainage lysimeters under protected environment conditions, using a Regolithic Neosol with sandy loam texture. Treatments res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Similarly, Sá et al (2019) observed a decrease in the longitudinal diameter and mass of fruits of 'BRS Jaburu' irrigated by water with salinity ranging from 0.6 to 3.8 dS m -1 at 365 days after transplanting. Also, Lima et al (2019b) found a reduction in the average fruit mass of this cultivar caused by irrigation with ECw from 3.8 dS m -1 at 515 days after transplanting.…”
Section: Source Of Variationmentioning
confidence: 70%
See 1 more Smart Citation
“…Similarly, Sá et al (2019) observed a decrease in the longitudinal diameter and mass of fruits of 'BRS Jaburu' irrigated by water with salinity ranging from 0.6 to 3.8 dS m -1 at 365 days after transplanting. Also, Lima et al (2019b) found a reduction in the average fruit mass of this cultivar caused by irrigation with ECw from 3.8 dS m -1 at 515 days after transplanting.…”
Section: Source Of Variationmentioning
confidence: 70%
“…Studies investigating the effect of irrigation water salinity between 0.6 and 3.8 dS m -1 has shown harmful effects of salt stress on photosynthesis, photochemical efficiency, water relations, growth, and production components of West Indian cherry (Sá et al, 2018a;2018b;2019;Lima et al, 2019a). Some studies have shown that the increase in potassium doses mitigated the deleterious effect of salt stress on plant growth, the number of fruits and total weight of fruits per plant (Lima et al, 2019b) and of nitrogen and phosphorus proportions on photochemical efficiency and growth (Sá et al, 2018a), photosynthetic pigments (Sá et al, 2018b), and the number of fruits per plant (Sá et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the Fm of plants subjected to salt stress is indicative that there was deficiency in the photoreduction of quinone A (Q A ) in the thylakoid membranes and inflow of electrons between the photosystems (Tatagiba et al, 2014). Reduction in maximum fluorescence as a function of salt stress has also been observed in other crops such as West Indian cherry (Dias et al, 2018), cashew (Lima et al, 2019), and in 'Mimo do Céu' orange (Sousa et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, this region commonly has high temperatures, low rainfall levels, irregular distribution of rains, and intense evaporation in most months of the year, which makes the practice of irrigation indispensable to ensure security in agricultural production (Lima et al, 2019). However, in the custard-apple growing region in the semiarid region of Northeast Brazil, most waters contain relatively high contents of salts, mainly those of sodium and chloride, being one of the main obstacles to agricultural production (Andrade et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation